Logic Model of Governance Innovation and Public Policy in Public Service - Lesmana Rian Andhika; Heru Nurasa; Nina Karlina; Candradewini Candradewini (Policy & Governance Review, 2018)
This research aims to provide additional qualitative evidence of the logical relationship between governance innovation and public policy in public services in Indonesia with adopting the logic model. The logic model is often not adopting in the formulation of policies that resulted in the implementation of public sector innovation such as cannot show more significant results. Also this model is believed to contribute in planning and evaluation of government programs. Most of this article based on the literature study and direct observation. The study also refers to some cases were chosen deliberately and treated as evidence by using a descriptive qualitative approach for developing an argument and conceptual framework accordingly. This research resulted in some information. First, governance innovation will provide multi-benefits, not only for the government but will involve a range of other institutions. Second, public policy is treated as a formal legal basis to keep programs planning and evaluation. That way this article is expected to contribute to the knowledge development of logical relationships among governance innovation and public policy in the diﬀerent local contexts Indonesia from countries which often becomes a reference in managing public service innovation.